The level of major urinary proteins is socially regulated in wild Mus musculus musculus - Janotova, Katerina; Stopka, Pavel (Journal of chemical ecology, 2011)
Major urinary proteins (MUPs) are highly polymorphic proteins that have been shown to perform several important functions in the chemical communication of the house mouse, Mus musculus. Production of these proteins in C57Bl/6 females is cyclic, reaching the maximum just before the beginning of estrus. Social environment is an important factor that increases MUP production in both sexes. We examined responsiveness of MUP production to social stimuli in wild mice, Mus musculus musculus. The direction of change of MUP production in males depended on the sex of the stimulus animal. Males up-regulated MUP production when caged with a female, but down-regulated MUP production when caged with a male. Down-regulation was more pronounced in males that were defeated in a male-male encounter. Females responded to a male's presence with a decrease in MUP production. We conclude that social modulation of MUP production is specific and, in coordination with other mechanisms, facilitates adjustment of the animal's odor profile to different social contexts. Our results also suggest that in males, MUPs may play an important role in advertizing the male's quality to females. Furthermore, we highlight the importance of analyzing data corrected with creatinine, which show MUP production on the (post)translational level as well as raw data (non-corrected with creatinine), which represent actual concentrations of MUPs in the urine.
Keywords: myši; Male; chování zvířat; Proteins; Species Specificity; sociální chování; proteiny; Mice; Up-Regulation; Animals; upregulace; zvířata; Social Behavior; mužské pohlaví; Behavior, Animal; Down-Regulation; ženské pohlaví; down regulace; Female; druhová specificita